Penguatan Literasi Digital dan Model Pembelajaran Jarak Jauh Inovatif untuk Meningkatkan Ketangguhan Masyarakat di Era Digital: Strengthening Digital Literacy and Innovative Distance Learning Models to Increase Community Resilience in the Digital Era - Thahira, Agniya; Tanjung, Afriansyah; Eliana, Desy; Setyaputri, Khairina Eka (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The article aims to describe the urgency, implementation, and impact of collaborative efforts in creating an innovative education ecosystem and a resilient society in the digital era. The digital era presents both opportunities and challenges for education and community resilience. Higher education institutions are required to develop innovative, inclusive, and sustainable distance learning (DL) models, while society, especially youth, faces a serious threat from the rise of online gambling. In response, Universitas Siber Muhammadiyah implemented a community service program at Pondok Pesantren Nur Ma'arif Sepang, Polewali Mandar, West Sulawesi, employing a participatory and collaborative approach. The program was implemented from February to June 2025, with its peak in a webinar held on May 25, 2025. The method included a needs assessment, the design of modules on digital literacy, legal awareness, mental health, and Islamic financial literacy, followed by workshops, training sessions, and mentoring sessions. The results showed a significant improvement in participants' knowledge, with average pretest scores of 68.20 increasing to 83.75 in the posttest. The most notable improvements were in legal understanding and Islamic financial literacy. Supporting factors included high participant enthusiasm, accessible learning materials, and the involvement of young tech-savvy teachers, while major obstacles were limited internet access and insufficient hardware. This program concludes that integrating innovative distance learning and digital literacy based on Islamic values can enhance youth resilience against digital disruption and strengthen pesantren's role as an agent of social change.